Mosaicos de la Comunidad (Mosaics of the Community): Community-Engaged Participatory Muraling with Madres Emprendedoras - Jesica Siham Fernández; Laura A. Nichols (Social Sciences)
In this paper, we describe a collaborative community-based research project that centered on community members’ lived experiences, which led to the identification of key community issues that resulted in a representative art project in the form of a public mural. Eleven mothers who were long-time residents of the community were the drivers of the issue identification and mural creation. The issues identified, and subsequently depicted in the mural, revealed the importance of the environment in neighborhoods, with residents dealing with encampments, illegal dumping, prostitution, eviction, and gentrification. In the mural Mosaicos de la Comunidad (Mosaics of the Community), a group of madres (mothers) sought to emphasize their shared admiration of art as a form of remembrance of ample food, clean air, and beautiful spaces to live and raise their children. Drawing from the madres’ reflections and written testimonials, this paper describes the collective mural-making process; moving from research-based issues identified by the madres into the mural design stage, including the identification of symbols and their meanings, to the creation and painting, and the culmination with a mural-unveiling celebration. The paper ends with a description of the value of community-based art as a form of resistance and as a reminder to concretize the environmental justice issues and values that are central to community members.